2007
DOI: 10.1111/j.1600-0765.2006.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The up‐regulation of type I plasminogen activator inhibitor in human gingival fibroblasts stimulated with cyclosporin A

Abstract: These findings suggest that the up-regulation of PAI-1 may play an important part in the molecular pathogenesis of cyclosporin A-induced gingival overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…CsA is one of the basic immunosuppressants for the prevention of transplant rejection as well as for the management of various autoimmune conditions. CsA was found to contribute to an important change in fibroblast function, and our studies have shown that the upregulation of plasminogen activator inhibitor‐1, 5,6 lysyl oxidase, 7 cystatin C, 8 heat shock protein 47, 9 and hypoxia‐inducible factor‐1α 10 may contribute directly or indirectly to extracellular matrix (ECM) accumulation in CsA‐induced gingival overgrowth. However, the exact mechanism whereby CsA induces gingival overgrowth still remains largely obscure.…”
mentioning
confidence: 85%
“…CsA is one of the basic immunosuppressants for the prevention of transplant rejection as well as for the management of various autoimmune conditions. CsA was found to contribute to an important change in fibroblast function, and our studies have shown that the upregulation of plasminogen activator inhibitor‐1, 5,6 lysyl oxidase, 7 cystatin C, 8 heat shock protein 47, 9 and hypoxia‐inducible factor‐1α 10 may contribute directly or indirectly to extracellular matrix (ECM) accumulation in CsA‐induced gingival overgrowth. However, the exact mechanism whereby CsA induces gingival overgrowth still remains largely obscure.…”
mentioning
confidence: 85%
“…12 Hypoxia could enhance fibrogenesis via PAI-1 protein involved in ECM modification. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 Recent results suggest that PAI-1 expression is significantly upregulated in CsA-induced gingival overgrowth specimens. 12 We have found that CsA could upregulate PAI-1 protein expression under hypoxia than normoxia. In addition, PAI-1 protein was markedly abolished by HIF-1a inbitior CAY10585 treatment under hypoxic condition.…”
Section: Inflammation Highmentioning
confidence: 98%
See 1 more Smart Citation
“…HGFs were cultured using an explant technique, as described previously. 4,8 Slug expression analysis HGFs were arrested in G 0 by serum deprivation according to our previous experiments. 7 Nearly confluent monolayers of HGFs were washed with a serum-free medium and immediately thereafter exposed, at indicated incubation times, to 0 ng/mL, 100 ng/mL, 200 ng/mL, 500 ng/mL, and 1000 ng/mL CsA (Sigma-Aldrich, St Louis, MO, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%